Digital Comic Learning Media Based on Subak Local Wisdom to Increase Students' Interest in Learning on the Topic of the Water Cycle in Grade V Elementary School - Ketut Satya Wacika Diatmika; Nice Maylani Asril; Ni Wayan Rati (Jurnal Pendidikan Multikultural Indonesia, 2025)
This study was motivated by the limited availability of learning media owned by teachers, which has an impact on students’ low interest in learning science. Therefore, this development research aims to develop digital comic learning media based on the local wisdom of Subak to increase the science learning interest of fifth-grade elementary school students on the topic of the water cycle. The subjects in this study involved two material experts, one media expert, one practitioner (class teacher), and fifteen fifth-grade elementary school students as trial participants. This research used the 4D development model (Define, Design, Develop, and Disseminate), focusing on the design, validity, practicality, and effectiveness of the media. Data were collected through questionnaires and assessments from experts, as well as pre-test and post-test trials. Data analysis used descriptive quantitative analysis and a t-test (paired sample t-test). The results showed that the media was categorized as very valid, with scores of 96% from material experts, 90% from the media expert, and 95.5% from the practitioner. Student responses were very positive, with a score of 96.8%, and there was a significant increase in learning interest based on the t-test results (sig. 0.00 < 0.05). The conclusion of this study is that the Subak-based digital comic media is feasible and effective for use. The implication is that this media can serve as an innovative alternative to support contextual and enjoyable science learning.